A novel experimental system using the liverwort Marchantia polymorpha and its fungal endophytes reveals diverse and context‐dependent effects. Issue 3 (7th February 2018) - Nelson, Jessica M.; Hauser, Duncan A.; Hinson, Rosemary; Shaw, A. Jonathan
Summary: Fungal symbioses are ubiquitous in plants, but their effects have mostly been studied in seed plants. This study aimed to assess the diversity of fungal endophyte effects in a bryophyte and identify factors contributing to the variability of outcomes in these interactions. Fungal endophyte cultures and axenic liverwort clones were isolated from wild populations of the liverwort, Marchantia polymorpha . These collections were combined in a gnotobiotic system to test the effects of fungal isolates on the growth rates of hosts under laboratory conditions. Under the experimental conditions, fungi isolated from M. polymorpha ranged from aggressively pathogenic to strongly growth‐promoting, but the majority of isolates caused no detectable change in host growth. Growth promotion by selected fungi depended on nutrient concentrations and was inhibited by coinoculation with multiple fungi. The M. polymorpha endophyte system expands the resources for this model liverwort. The experiments presented here demonstrate a wealth of diversity in fungal interactions even in a host reported to lack standard mycorrhizal symbiosis. In addition, they show that some known pathogens of vascular plants live in M. polymorpha and can confer benefits to this nonvascular host. This highlights the importance of studying endophyte effects across the plant tree of life. Abstract : See also the Commentary on this article byRich & Delaux, 218 : 882–884 .